2015
DOI: 10.1021/bc500524f
|View full text |Cite
|
Sign up to set email alerts
|

Interface of Physics and Biology: Engineering Virus-Based Nanoparticles for Biophotonics

Abstract: Virus-based nanoparticles (VNPs) have been used for a wide range of applications, spanning basic materials science and translational medicine. Their propensity to self-assemble into precise structures that offer a three-dimensional scaffold for functionalization has led to their use as optical contrast agents and related biophotonics applications. A number of fluorescently labeled platforms have been developed and their utility in optical imaging demonstrated, yet their optical properties have not been investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 43 publications
(70 reference statements)
1
68
0
1
Order By: Relevance
“…Effective cell killing of the covalently-delivered DOX for the DOX TMV and DOX SNP formulations can be explained by the intracellular fates of the protein-based nanocarrier: in previous cellular trafficking experiments we have shown that TMV is internalized by cancer cells through endocytosis and targeted to the endolysosome, where the free drug is released following degradation of the proteinaceous carrier [56,57]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective cell killing of the covalently-delivered DOX for the DOX TMV and DOX SNP formulations can be explained by the intracellular fates of the protein-based nanocarrier: in previous cellular trafficking experiments we have shown that TMV is internalized by cancer cells through endocytosis and targeted to the endolysosome, where the free drug is released following degradation of the proteinaceous carrier [56,57]. …”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous studies on cell trafficking of TMV [56, 57], it is expected that upon cell targeting and internalization, the protein-based carriers are targeted to the endolysosomal compartment, where the proteinaceous plant virus-based carriers will be metabolically degraded through hydrolase and protease activity, therefore yielding efficient drug release inducing effective cell killing. Indeed our data confirmed that drug efficacy was maintained upon conjugation to or encapsulation into the TMV and SNP-based carriers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…66 A second investigation into CPMV as a fluorescence agent for biological imaging suggests that surface dye labeling density can affect the observed fluorescence intensity as well as the cell−virus interactions. 73 CPMV nanoparticles were modified with Cy5 dyes at various ratios to elucidate the optimal amount of dye for loading. They found that 27 dyes per CPMV particle yielded maximal fluorescence, after which quenching occurs.…”
Section: Molecular Interactions To Enhance Fluorescence Imagingmentioning
confidence: 99%
“…These results are as expected, as we and others have previously shown that TMV is internalized by cancer cells through a combination of endocytosis and macropinocytosis and that the particles then co-localize with endolysosomal markers. [28][29][30] We hypothesize that within the protease-rich environment of the endolyosome, the prodrug TMV-vcMMAE is cleaved at the protease-cleavable vc linker, resulting in release of the active MMAE component. In fact, in our previous studies, we have shown that TMV-conjugated cargos are cleaved and released in endolysosomal extracts even when conjugated via amide bonds.…”
Section: Resultsmentioning
confidence: 99%